Answer:
∠C ≅ ∠M or ∠B ≅ ∠L
Step-by-step explanation:
You are given an angle and its opposite side as being congruent. AAS requires two congruent angles and one side, so you need another set of congruent angles (one in each triangle). It does not matter which they are. The above-listed pairs are appropriate.*
_____
* Since the figure cannot be assumed to be drawn to scale, either of angles B or C could be declared congruent to either of angles L or M. However, it appears that angles B and L are opposite the longest side of the triangle, so it makes good sense to declare that pair congruent. The same congruence statement (ΔBCD≅ΔLMN) would result from declaring angles C and M congruent. So, either declaration will work (matches the last answer choice.)
__
AAS requires two angles and a side. One side is already marked, so we do not need any more information about sides. (The second and third answer choices can be rejected as irrelevant.)
Let's solve your equation step-by-step.
9x=10
Step 1: Divide both sides by 9.
9x / 9 = 10 /9
x = 10 / 9
Answer:
x = 10 / 9
The answer is 57 because using remote angles theorem you get the largest angle equals to 66 degrees but you are not done yet you have to subtract 66 from 180 because of sum of angles in a triangle so you get 114 degrees and since you have an isosceles triangle you have to divide by two to get y so y = 57 degrees
The probability is 56/100, or 14/25 = 0.56.
These events are not mutually exclusive, meaning they can happen at the same time. This means we use
P(A or B) = P(A) + P(B) - P(A and B)
P(carpool or full time) = P(carpool) + P(full time) - P(carpool & full time)
There are 6+9=15 people out of 100 that carpool.
There are 7+4+30+6=47 people out of 100 that work full time.
There are 6 people out of 100 that carpool and work full time.
This gives us
15/100 + 47/100 - 6/100 = 56/100
Answer:
x = -2, y = 3
Step-by-step explanation:
Given equations are,
4x + 5y = 7 ---------(1)
3x - 2y = -12 ----------(2)
Multiply equation (1) by 3
12x + 15y = 21 ------(3)
Multiply equation (2) by (-4)
-12x + 8y = 48 --------(4)
Now add equations (3) and (4),
(12x + 15y) + (-12x + 8y) = 21 + 48
(12x - 12x) + (15y + 8y) = 69
23y = 69
y = 3
From equation (2),
3x - 2(3) = -12
3x - 6 = -12
3x = 6 - 12
x = -2
Therefore, x = -2 and y = 3 will be the answer.